Workshop: Participatory Research Tools Latin America - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
In this workshop, local partners from various central american countries worked with the tools of the CCAFS Gender and Inclusion Toolbox. The workshop took place in Matagalpa, Nicaragua in November, 2014. The Toolbox can be downloaded from https://cgspace.cgiar.org/bitstream/handle/10568/45955/CCAFS_Gender_Toolbox.pdf?sequence=7